Planning of coal production taking into account the intensity of shipment and the capacity of transport routes - Tyurin Alexey (EDP Sciences, 2021)
For effective planning of coal mining at coal mines, it is necessary to take into account the relationship between internal and external processes that occur from the moment of mining the coal to the moment of its sale to consumers. Internal processes are primarily determined by the coordination of operations for drilling and blasting operations, the excavation of mined rock into dumps, the movement of coal to warehouses, its washing and further shipment to railway wagons. External processes are determined by ensuring the delivery of coal to consumers, taking into account the capacity of transport routes, the demand for coal and the price policy in export markets that develops in a certain period of time. Using the example of coal companies that are part of JSC Kuzbassrazrezugol, the article considers a two-level dynamic model for planning coal production, taking into account the intensity of shipment and the capacity of transport routes. At the first level, the volume of coal production intended for export is determined by month, taking into account the intensity of demand for the periods of the year and all restrictions that affect the speed of coal movement to the consumer. At the second level of the system under consideration, the volume of coal sales for export is redistributed over a single time period, taking into account the limitations in the capacity of transport routes, the speed of cargo delivery to the consumer, the level of demand and prices for coal. The use of the dynamic programming method made it possible to solve the problem of redistributing coal sales volumes for export at the second level and, using the results of solving this problem, to determine the optimal volumes of coal production intended for export at the first level.